2019
DOI: 10.3889/oamjms.2019.631
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Multiple Anterior Cervical Discectomy with Cage Fusion Technique: Results of Multiple Centre Study

Abstract: BACKGROUND:Cervical herniation is commonly treated by anterior cervical discectomy and fusion (ACDF) if conservative management has failed in relief of the patient’s symptoms. Disc fusion is needed after ACDF as anterior longitudinal ligament will be absent after doing the operation, especially if multiple levels are needed. The occurrence of complications as cage subsidence and adjacent segment failure related to the length of follow up as they are increasing in percentage is directly proportional to the leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Male patients were more than female patients [21], [23] unlike other two studies that had the https://oamjms.eu/index.php/mjms/index number of females more than that of males [12], [22]; this reveals that the difference in gender distribution shows no significance and no direct relation to development of ASD.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Male patients were more than female patients [21], [23] unlike other two studies that had the https://oamjms.eu/index.php/mjms/index number of females more than that of males [12], [22]; this reveals that the difference in gender distribution shows no significance and no direct relation to development of ASD.…”
Section: Discussionmentioning
confidence: 63%
“…The age did not show statistical significance; all studies think that ASD could occur at any age, supporting the fact that cervical degenerative disease is an aging process but it has no direct effect on the timing of neither surgery nor its outcome [12], [21], [22], [23].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Sun et al [34] performed a 5-year 3-level ACDF study and found 81 surgical levels were completely fused at the 5-year follow-up, but six levels remained unfused in the rst year after surgery. In a similar three-year study [35], the fusion rates at 1, 2, and 3 years after surgery were 77.9%, 94.1%, and 100%, respectively. In another study [36] involving 78 patients who also used the spinous processes criteria to assess fusion rate, all surgical levels were fused within the rst year.…”
Section: Fusionmentioning
confidence: 78%
“…However, few studies reported surgical, clinical, and radiologic outcomes after three-level contiguous ACDF without plating. 7,[9][10][11][12][13] This study aimed to investigate long-term clinical and radiological outcomes and complication rate after threelevel contiguous ACDF without plating for cervical DDD.…”
Section: Introductionmentioning
confidence: 99%